2006
DOI: 10.1063/1.2162052
|View full text |Cite
|
Sign up to set email alerts
|

Principal physics of rotating magnetic-field current drive of field reversed configurations

Abstract: After extensive experimentation on the Translation, Confinement, and Sustainment rotating magnetic-field (RMF)-driven field reversed configuration (FRC) device [A. L. Hoffman et al., Fusion Sci. Technol. 41, 92 (2002)], the principal physics of RMF formation and sustainment of standard prolate FRCs inside a flux conserver is reasonably well understood. If the RMF magnitude Bω at a given frequency ω is high enough compared to other experimental parameters, it will drive the outer electrons of a plasma column in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…The TCS parameters in Table I, taken from a publication, 18 are for one of its best performing RM F e discharges, having achieved a steadystate electron temperature near 50 eV atn e = 1.3 × 10 13 cm −3 . Measurements showed that the RM F e only penetrated ∼ 10 cm into the plasma, to about the O-point line.…”
Section: Numerical Results For Ion Heatingmentioning
confidence: 99%
“…The TCS parameters in Table I, taken from a publication, 18 are for one of its best performing RM F e discharges, having achieved a steadystate electron temperature near 50 eV atn e = 1.3 × 10 13 cm −3 . Measurements showed that the RM F e only penetrated ∼ 10 cm into the plasma, to about the O-point line.…”
Section: Numerical Results For Ion Heatingmentioning
confidence: 99%
“…RMF current drive 10,23 is the most heavily studied and successful method for sustaining a prolate FRC ͑prolate FRCs have elongation E = Z S / R S Ͼ 1, where Z S and R S are the maximum axial and radial locations on the separatrix͒. This technique was developed in a series of rotomak experiments at Flinders University, 12 and has subsequently been applied to the prolate FRC with good success.…”
Section: A Frc Sustainmentmentioning
confidence: 99%
“…A first experiment in STX ͑Star Thrust Experiment͒ was able to generate axial field reversal significantly larger than the magnitude of the rotating field, 14 and to maintain the field-reversed configuration for as long as the RMF was applied, and subsequent experiments have expanded the operational regime and physics basis of this technique. It has been applied both to sustain a plasma formed by theta-pinch initiation 14 and to form an FRC from a uniform axial field with a pre-ionized fill; 17,20 it has sustained the configuration when the antennas were located outside of an insulating vacuum chamber, 23 or inside an all-metal chamber. 22 RMF applies a rotating transverse magnetic field to the plasma, leading to a time-dependent axial electric field.…”
Section: A Frc Sustainmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of spheromak plasmas has been demonstrated via many different methods, 4 including flux-cores, 16 coaxial plasma guns, 17 combined theta-and Z pinches, 18 conical theta-pinches, 19 kinked Z pinches, 20 and steady inductive helicity injection ͑SIHI͒. 21 The formation of axially elongated FRC plasmas has, however, been limited to rotating magnetic fields, 22 fast formation by theta-pinch coils, 5 and in a single case, a scheme known as the Coaxial Slow-Source. 23,24 Formation of oblate ͑more spherical͒ FRC plasmas has generally been limited to the merging of spheromaks, [25][26][27][28] or in a single case, a laser produced plasma coupled to fast coil ramps.…”
Section: Introductionmentioning
confidence: 99%